The Impact of Bullying on the Development of Mental Health in Children - Ira Aini Dania; Nanda Novziransyah; Adi Raja Brando Lubis (Gema Lingkungan Kesehatan, 2024)
The occurrence of bullying behavior within SDN Bhakti Karya Jogja has the potential to create an environment that is detrimental to the physical and mental development of children. The observed bullying behavior within this context can be categorized as either physical or non-physical/verbal. The bullying observed in this study arises from misunderstandings and minor issues that have a significant impact on the mental wellbeing of those subjected to it. This study employs a qualitative approach in the form of a case study methodology. The research findings indicate that the forms of verbal bullying observed at SDN Bhakti Karya Jogja include slandering the victim and the victim's parents, mocking, threatening, and using profanity. With regard to the forms of physical bullying, these include hitting, taking things, and pinching. It can be observed that victims of bullying exhibit signs of distress. They become quiet, weak, afraid when they meet the perpetrators and tired of the perpetrators’ treatment. Additionally, they become markedly moody and disinterested in learning. Educational institutions have implemented a variety of strategies in response to bullying behavior. These include counseling, disciplinary measures, and the integration of early religious education into the curriculum. Furthermore, the incorporation of character education, comprising curricula designed to instill positive values and behaviors, has gained prominence as a strategy to promote constructive social interactions. Additionally, educational establishments have sought to utilize students' leisure time in productive endeavors, such as the provision of engaging learning activities.